PENINGKATAN NILAI-NILAI AGAMA DAN MORAL PADA ANAK KELOMPOK B BERAGAMA HINDU MELALUI METODE BERCERITA DI TK TUNAS BANGSA TENGGARONG SEBERANG TAHUN PELAJARAN 2018/2019 - Desak Made Kusuma Wardani; Mahkamah - Brantasari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2019)
The background of this study is based on the results of temporary observation that show the children of Tunas Bangsa Kindergarten Tenggarong Seberang, especially in Hindu childrengroup B, have varied problems such as in knowing religion, correct prayer attitude, saying greetings, behaving properly and polite, say a prayer before and after learning. The children are not familiar with habituation itself, so teachers need to set an example for children to get used to religious and moral values in school. Based on these problems, the researcher made a modification in learning activities by applying the method of storytelling. The purpose of this research is to find out the improvement of religious and moral values in Hindu children group B through storytelling method in Tunas Bangsa Kindergarten Tenggarong Seberang inAcademic Year 2018/2019. This is a Classroom Action Research (CAR), with several stages namely planning, implementation, observation and reflection. This research was conducted in two cycles, each cycle consisting of 3 actions. The initial condition or the first cycle (pre-action) only reached 68%, at the 2nd meeting; they experienced an improvement to 70% and at the 3rd meeting, students experienced improvement as the average reaches 73%. In the second cycle stage, at the 1st meeting, students on average experienced an improvement of religious and moral values to 76%, and then increased at the 2nd meeting to 79%, and at the 3rd meeting, another increase in students to 81 %. This means that by using the method of storytelling, it can improve the religious and moral values of children and teachers are successful in the process of learning and teaching in the Tunas Bangsa Tenggarong Seberang.